SYNTHESIS, STRUCTURAL STUDY AND ANTIBACTERIAL ACTIVITY OF SOME NEW COMPLEXES WITH 2-N(4-N,N-DIMETHYL BENZYLIDEN)-5-(P-IODO PHENYL)-1,3,4-THIODIAZOLE WITH Cr (III), Mn (II), and Cd (II) IONS - Bakir, Sh R; Kareem, T A A; Alias, M F (Al-Nahrain Journal of Science, 2010)
A new Schiff base 2-N(4-N,N-dimethyl benzyliden)-5-(p-Iodo phenyl)-1,3,4-thiodiazol and itsmetal complexes with Cr(III), Mn(II), and Cd (II) ions , were synthesized . The prepared complexeswere identified and their structural geometries were suggested by using flame atomic absorptiontechnique, FT-IR and Uv-vis Spectroscopy, in addition to Magnetic Susceptibility and Conductivitymeasurements .Different bonding and structural behavior were revealed through the study of thecoordination chemistry of the metal complexes of the ligand. The nature of bonding between themetal ion and the donor atoms of the ligand were demonstrated through the calculated of Racahparameter and the other ligand field parameters which were calculated by using suitableTanaba-Sugano-diagrams .Structural geometries of these compounds were also suggested in gasphase by using theoretical treatments, using Hyper chem-6 program for the molecular mechanicsand semi-empirical calculations. The heat of formation (ΔHf◦) and binding energy (ΔEb)for the freeligand and it’s metal complexes were calculated by PM3 methods.The antibacterial activity for the ligand and its metal complexes were studied against twoselected microorganisms (Staphylococcus aureus) as gram positive and (Pseudomonasaeruginosa) as gram negative.